2012
DOI: 10.1074/jbc.m112.363226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-Acetylaspartylglutamate (NAAG) Peptidase Inhibition on Release of Glutamate and Dopamine in Prefrontal Cortex and Nucleus Accumbens in Phencyclidine Model of Schizophrenia

Abstract: Background: Inhibitors of the enzyme that inactivates the peptide transmitter N-acetylaspartylglutamate reduce behaviors induced by PCP in animal models of schizophrenia. Results: NAAG peptidase inhibition reduces PCP-induced glutamate release in two brain areas implicated in this disorder. Conclusion: Peptidase-mediated inhibition of glutamate release is consistent with the glutamate model of this disorder. Significance: NAAG peptidase inhibitors warrant further biochemical characterization as potential antip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 60 publications
(62 reference statements)
3
35
0
Order By: Relevance
“…These data suggest that GCPII inhibition increases NAAG, which in turn mediates its effects predominantly, if not exclusively, via mGluR3 to the resultant alleviation of pain. However, it remains possible that NAAG attenuates the excitability of postsynaptic neurons by interfering with the binding of released glutamate at the N-methyl-D-aspartate receptor as suggested previously (Carpenter et al, 2003), although this effect may be indirect (Zuo et al, 2012) and remains controversial (Losi et al, 2004). It should also be noted that the analgesic effects of NAAG (mediated directly or via GCPII inhibition) may be at least partially caused by interactions with other transmitters in the ascending and descending pathways .…”
Section: Discussionmentioning
confidence: 94%
“…These data suggest that GCPII inhibition increases NAAG, which in turn mediates its effects predominantly, if not exclusively, via mGluR3 to the resultant alleviation of pain. However, it remains possible that NAAG attenuates the excitability of postsynaptic neurons by interfering with the binding of released glutamate at the N-methyl-D-aspartate receptor as suggested previously (Carpenter et al, 2003), although this effect may be indirect (Zuo et al, 2012) and remains controversial (Losi et al, 2004). It should also be noted that the analgesic effects of NAAG (mediated directly or via GCPII inhibition) may be at least partially caused by interactions with other transmitters in the ascending and descending pathways .…”
Section: Discussionmentioning
confidence: 94%
“…We did not find major differences in the spontaneous behavior of wild type and Abcc5 Ϫ/Ϫ mice using an automated home cage monitoring system that monitors various aspects of behavior (26), however. Zuo et al (71) previously showed that pharmacological inhibition of GCP2 results in increased NAAG levels and reduced phencyclidine-induced locomotor activity in an animal model for schizophrenia. Such a difference was not found between our wild type and Abcc5 Ϫ/Ϫ mice, however (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…2-PMPA was shown to possess therapeutic efficacy in various preclinical models, including ischemia (Slusher et al, 1999), spinal cord injury (Long et al, 2005), neuropathic pain (Jackson et al, 2001;Wozniak et al, 2012), cocaine addiction (Xi et al, 2010a;Xi et al, 2010b), and schizophrenia (Olszewski et al, 2008;Zuo et al, 2012). Thus, GCP-II inhibition may provide broad therapeutic utility in neurologic diseases especially where excess glutamate is presumed pathogenic (Rojas et al, 2011;Ba rinka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%